Preliminary Study on Rainfall Interception through Leaflitter - Pradhan, J. P. (Indian Forester, 1973)
A preliminary study on interception through the leaflitter of live different forest species was observed at Soil Conservation Research Farm, Vasad. High average interception was found through the leaflitter of Tectona grandis. (26.83%) and Acacia arabica (24.51%), while that of Dendrocalamus strictus (23.61%) and Dalbergia sissoo (22.19%) gave low interception and the lowest was through the leaflitter of Albi ia lebbek (17.68%). Out of the tree species under study, highest interception of rainwater was through the leaflitter of Tectona grandis (broad leaved) and out of leguminous species the leaflitter of Acacia arabica gave higher interception. Observation revealed that besides the nature of leaflitter, interception depends upon tbe rainfall characteristics and prevailing weather conditions. Prolonged low rainfall creates condition of saturation deficit to the volume of litter mass. When one kilogram leaflitter of each of the above species was allowed to intercept 1448 mm rainfall throughout the rainy season of 48 rainy days, more decomposition of litter mass was found In Tectona grandis (47.1%) and that of Acacia arabica (43.5%) was the least.